If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4x = x Combine like terms: 6x + -4x = 2x 2x = x Solving 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 1x = x + -1x Combine like terms: x + -1x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 0.5(x+2)-0.7(x+2)=-0.2x-0.4 | | 81x=0 | | 7x^2-27x=0 | | 16x=-65 | | x^2=-2x+8 | | 3a+2(a-4)= | | 2(x+5)-9= | | 8-3x=6-8x | | 25+x=-11 | | -3(6p+3)-2(2-17p)=3(5+5p) | | 4x+16=x+0 | | -6(w-1)= | | -4(3-2)-(-3-5x)=2(x-3x-1) | | 2(5x+1)= | | 4x+81=81 | | 64x+49=49 | | x-36x= | | 6-5x+3=7-5x | | 2a-9=2(a+1)+14a+4 | | 3y-2=18-8y | | 5(t-4)+3t=4(2t+4)-12 | | 3(x-2)-2(x+7)=2x+17 | | 9x+5(0)=90 | | (2z+6)+(4z-3)=(5z+12) | | .25+2b=13+5b | | 9(5)+5y=90 | | 9(0)+5y=90 | | 10x+11=9x+3 | | x-0.5z=-25 | | x+2z=200 | | h(x)=0.5x+3 | | 3x(x^2-7x-5)= |